2016
DOI: 10.1016/j.ebiom.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic With or Without Fiber Controls Body Fat Mass, Associated With Serum Zonulin, in Overweight and Obese Adults—Randomized Controlled Trial

Abstract: BackgroundThe gut microbiota is interlinked with obesity, but direct evidence of effects of its modulation on body fat mass is still scarce. We investigated the possible effects of Bifidobacterium animalisssp. lactis 420 (B420) and the dietary fiber Litesse® Ultra polydextrose (LU) on body fat mass and other obesity-related parameters.Methods225 healthy volunteers (healthy, BMI 28–34.9) were randomized into four groups (1:1:1:1), using a computer-generated sequence, for 6 months of double-blind, parallel treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 51 publications
5
118
2
4
Order By: Relevance
“…To some extent, these findings indicate that RYGB induced a reduction in inflammation independent of diet control. In this study we did not include a body weight‐matched control group to interpret the extent to which RYGB could reduce intestinal permeability and inflammation; however, in the PF group, partial correction of overweight by dietary limitation was seen to correct the intestinal barrier defect, consistent with previous reports …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To some extent, these findings indicate that RYGB induced a reduction in inflammation independent of diet control. In this study we did not include a body weight‐matched control group to interpret the extent to which RYGB could reduce intestinal permeability and inflammation; however, in the PF group, partial correction of overweight by dietary limitation was seen to correct the intestinal barrier defect, consistent with previous reports …”
Section: Discussionsupporting
confidence: 84%
“…In this study we did not include a body weight-matched control group to interpret the extent to which RYGB could reduce intestinal permeability and inflammation; however, in the PF group, partial correction of overweight by dietary limitation was seen to correct the intestinal barrier defect, consistent with previous reports. 25,26 Leakage of gut microbiota-derived LPS into the blood induces metabolic endotoxemia, which triggers enhanced inflammation and oxidative stress. 27 Nevertheless, in our previous and other's studies, 4,12 RYGB was shown to induce a markedly higher relative abundance of Proteobacteria, Gammaproteobacteria, and Betaproteobacteria and increased emergence of Fusobacteria and Clostridium, which belong to the Gram-negative bacteria and have been speculated to account for 80% of LPS concentrations in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the Lac/Man test may not be sensitive enough to detect ongoing functional barrier defects (as measured by persistent high fecal zonulin concentrations) that still cause LPS trafficking. These results are also at odds with another recent report that showed that a reduction in body fat mass in obese adults by targeting the gut microbiota through prebiotic and probiotic administration rather than dietary intervention was significantly correlated with serum zonulin concentrations (10).…”
contrasting
confidence: 56%
“…Synbiotics, a synergistic combination of probiotics and prebiotics, are expected to have a greater effect on the health of the host than when each is used alone, and many clinical studies of synbiotics have been conducted (Asemi, Khorrami-Rad, Alizadeh, Shakeri, & Esmaillzadeh, 2014;Childs et al, 2014;Stenman et al, 2016;Waitzberg et al, 2013). However, these reports have not shown that synbiotics have a clearly stronger effect on the numbers of intestinal bifidobacteria compared with the use of probiotics or prebiotics alone.…”
Section: Discussionmentioning
confidence: 99%